2014
DOI: 10.1159/000368613
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Asthma Prevalence and Severity in Israel over a 10-Year Period

Abstract: Background: The prevalence of asthma has increased in western countries towards the end of the last century, but recently seems to have stabilized. Objective: To evaluate trends in the prevalence and severity of asthma that occurred in Israel over the past decade. Methods: The medical records of 17-year-old boys, eligible for national service, between 1999 and 2008 were reviewed. National annual hospitalization and death rates for asthma were extracted. Results: Three hundred thousand medical records were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Seven studies regarding the prevalence of asthma in Israel showed reduction of its prevalence with increased age . Genetic, ethnic, environmental and nutritional factors were suggested to be risk factors for the prevalence of asthma .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies regarding the prevalence of asthma in Israel showed reduction of its prevalence with increased age . Genetic, ethnic, environmental and nutritional factors were suggested to be risk factors for the prevalence of asthma .…”
Section: Resultsmentioning
confidence: 99%
“…Genetic, ethnic, environmental and nutritional factors were suggested to be risk factors for the prevalence of asthma . Asthma prevalence and wheeze were also increased from 1980 to1989 and from 1986 to 1990 but asthma ever prevalence was decreased from 1999 to 2008 . The results of two studies about the prevalence of asthma in Jordan indicated its prevalence of 8.7–10% in 6–7 years, 4.1% in 6–12 years and 8.8–9.5% in 13–14 years childeren .…”
Section: Resultsmentioning
confidence: 99%
“…Although the prevalence of allergic diseases differs between countries, general increases in prevalence have been reported for several decades, at least in industrialised countries . In recent years, some reports have suggested that the increase in the prevalence of asthma is levelling off , whereas others report an ongoing increase in both asthma and allergic rhinitis among children . It is unlikely that the pattern of changes will be similar in all countries and all parts of the world, but following the time trends of allergic diseases in a specific area, using the same questionnaires and methods, it can give information not only on the changes per se , but also may give vital clues on underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, specific public health strategies to protect vulnerable populations as subjects with asthma should be pursued. Although the global prevalence of asthma has been rising worldwide, some studies have shown that the number of hospitalizations tend to fall in some developed countries [2,3], at least partially explained by improved medical care and wide access to controller therapy, such as inhaled corticosteroids (ICS) [2,4].…”
Section: Introductionmentioning
confidence: 99%